Pengaruh Model Pembelajaran Generatif Berbantuan Media Laboratorium Virtual Terhadap Penguasaan Konsep Fisika Siswa pada Materi Momentum dan Impuls - I Nyoman Sugiana; Ahmad Harjono; Hairunnisyah Sahidu; Gunawan Gunawan (Jurnal Pendidikan Fisika dan Teknologi (JPFT), 2016)
This Ã¢â¬Ånon-equivalent control group designÃ¢â¬Â quasi experimental research was purposed to identify the effect of generative-based learning model using virtual laboratory media towards the studentsÃ¢â¬â¢ concept mastery and creativity in physics. The population of this research is all 173 students of X grade in SMK Negeri 7 Mataram. The X grade students of Teknik Komputer Jaringan A (TKJ-A) department was determined as the experimental group and the X grade students of Teknik Komputer Jaringan B (TKJ-B) department was the control group. The way of collecting data for the concept mastery was done by using multiple choice test. The result revealed that the mean score of the post-test for the concept mastery was 43 for the experimental group with the highest score 56. Meanwhile the mean score of the control group was 36 with the highest score 52. The research hypothesis was tested using t-test pooled variances. The result showed that the value of ttab is higher than tarith the value is 3,42 > 2,00 for the concept mastery. As the conclusion, this research showed that there was an effect towards the experimental group studentsÃ¢â¬â¢ concept mastery and creativity in physics which was treated using generative-based learning model using virtual laboratory media.